Was denkt die Agrarbranche über Pflanzenschutz wirklich? Ergebnisse eines impliziten Assoziationstests; What Does the Agricultural Sector really Think about Crop Protection? Results of an Implicit Association Test - Ulf Rom̈er; Henning Schaak; Oliver Mußhoff; Heinrich S. Goudschaal (German Journal of Agricultural Economics (GJAE), 2019)
– Chemical plant protection and protection by genetic modification of crops are being discussed controversially by the public as well as by the agri-food industry itself. However, attitudes towards different methods of plant protection have so far only been studied by standard surveys, which may provide a biased or incomplete picture. This study contributes information about the perception of different methods of plant protection by examining explicit as well as implicit attitudes of agricultural students - the future producers and decision-makers of the agricultural sector. The implicit attitudes were measured using a Single-Category Implicit Association Test. The test was conducted with 233 agricultural students. The results show that agricultural students assess chemical crop protection and protection by genetic modification of crops positively in a direct survey, but show negative attitudes in the case of implicit measurement. This indicates that opinions in the controversial crop protection debate, thus far solely assessed based on surveys, should be critically reviewed.
Keywords: 330